Relation of a hypoxia metagene derived from head and neck cancer to prognosis of multiple cancers - Winter, Stuart C; Buffa, Francesca M; Silva, Priyamal; Miller, Crispin; Valentine, Helen R; Turley, Helen; Shah, Ketan A; Cox, Graham J; Corbridge, Rogan J; Homer, Jarrod J; Musgrove, Brian; Slevin, Nick; et al. (Cancer research (Chicago, Ill.), 2007)
Affymetrix U133plus2 GeneChips were used to profile 59 head and neck squamous cell cancers. A hypoxia metagene was obtained by analysis of genes whose in vivo expression clustered with the expression of 10 well-known hypoxia-regulated genes (e.g., CA9, GLUT1, and VEGF). To minimize random aggregation, strongly correlated up-regulated genes appearing in >50% of clusters defined a signature comprising 99 genes, of which 27% were previously known to be hypoxia associated. The median RNA expression of the 99 genes in the signature was an independent prognostic factor for recurrence-free survival in a publicly available head and neck cancer data set, outdoing the original intrinsic classifier. In a published breast cancer series, the hypoxia signature was a significant prognostic factor for overall survival independent of clinicopathologic risk factors and a trained profile. The work highlights the validity and potential of using data from analysis of in vitro stress pathways for deriving a biological metagene/gene signature in vivo.